The Definition of the Crime of Helping Letter in Payment and Settlement: Social Factor Analysis - Lu, Siqi (International Journal of Social Sciences and Public Administration, 2024)
After investigation, the crime of helping the letter can be divided into subjective intention and non-subjective intention. Some people only collect personal information and do not participate in the payment and settlement. This phenomenon is more common in the society, especially in the economically underdeveloped areas and low-income groups. Some college students are also affected by their lack of awareness of crime, resulting in too broad conviction. In the conviction and sentencing, consideration should be given to different circumstances, paying special attention to the non-intentional but serious circumstances and the influence of network communication. When dealing with the payment and settlement information network crime, it is necessary to judge from the three dimensions of participation time, people involved and helping behavior. Those who know that others have committed a crime and provide help and the circumstances are serious shall be investigated for criminal responsibility. This paper will be analyzed from the above perspective.